2020
DOI: 10.1038/s41598-020-72813-x
|View full text |Cite
|
Sign up to set email alerts
|

Density-based classification in diabetic retinopathy through thickness of retinal layers from optical coherence tomography

Abstract: Diabetic retinopathy (DR) is a severe retinal disorder that can lead to vision loss, however, its underlying mechanism has not been fully understood. Previous studies have taken advantage of Optical Coherence Tomography (OCT) and shown that the thickness of individual retinal layers are affected in patients with DR. However, most studies analyzed the thickness by calculating summary statistics from retinal thickness maps of the macula region. This study aims to apply a density function-based statistical framew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…However, the GCL thickness was lesser in patients without DR compared with that in the controls. Mohammed et al reported that the GCL demonstrated the difference in its thickness in patients with DR versus that in controls [34]. In the present study, we found that the IPL thickness was similar in patients with and without DR but lower than that in the control group; however, the difference was not statistically signi cant.…”
Section: Resultscontrasting
confidence: 66%
See 2 more Smart Citations
“…However, the GCL thickness was lesser in patients without DR compared with that in the controls. Mohammed et al reported that the GCL demonstrated the difference in its thickness in patients with DR versus that in controls [34]. In the present study, we found that the IPL thickness was similar in patients with and without DR but lower than that in the control group; however, the difference was not statistically signi cant.…”
Section: Resultscontrasting
confidence: 66%
“…Mohammed et al, in their study, suggested that the change in the INL thickness is the best indicator that distinguishes patients with DR from controls; it has an even higher discriminative power than the early loss of RNFL thickness [34]. Changes in the INL were found to be more pronounced in animal studies [35].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The system had an AUC of . There are other works that use OCT to diagnose DR in [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This framework of permutation tests and classification models has also been successfully used for the analysis of imaging data in the context of diabetic retinopathy. 17,18…”
mentioning
confidence: 99%